Health education by ergonomic position coaching for back pain prevention in banana chips MSME’s workers - Nourmayansa Vidya Anggraini; Serri Hutahaean (Community Empowerment, 2022)
One of the problems that often occurs among workers is back pain. This non-ergonomic posture will also have an impact on skeletal muscle problems in the spine compared to the legs on a weight support. This community service is carried out by providing health education to banana chip MSME workers in Jakarta, totaling 30 workers. Before and after education, pretest and posttest were conducted. The purpose of this activity is to provide education to workers so as to avoid back pain. The results of the activity revealed an increase in the knowledge, attitudes and work behavior of the participants after participating health education.